2010
DOI: 10.1038/modpathol.2010.102
|View full text |Cite
|
Sign up to set email alerts
|

The immunohistochemical profile of Spitz nevi and conventional (non-Spitzoid) melanomas: a baseline study

Abstract: Several isolated markers have been proposed to aid in differential diagnostic of difficult melanocytic lesions, albeit none has been shown to be definitive in differentiating Spitz nevus from melanoma. This study proposes a wide panel of 22 markers having important functions in different biological functions (cell cycle, apoptosis, DNA repair proteins and membranous receptors) to provide a combination of proteins associated with either benign or malignant phenotype. Using tissue microarrays, we compared protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…CD99 has shown a diffuse expression in 56% of SMM, whereas only focal staining in 5% of SN . Carrido‐Ruiz et al . showed overexpression of p‐21 and cyclin D1 in SN, whereas low expression in non‐Spitzoid MM.…”
Section: Introductionmentioning
confidence: 99%
“…CD99 has shown a diffuse expression in 56% of SMM, whereas only focal staining in 5% of SN . Carrido‐Ruiz et al . showed overexpression of p‐21 and cyclin D1 in SN, whereas low expression in non‐Spitzoid MM.…”
Section: Introductionmentioning
confidence: 99%
“…3 We focused on 9p21 because there is growing evidence that copy number aberrations at the 9p21 chromosomal locus containing p16 INK4a and p14 ARF may be overrepresented in lesions with spitzoid morphology. 10,11,17 The 9p21 locus where the CDKN2A gene is located has long been recognized as a key player in melanoma. The CDKN2A gene by means of an alternative reading frame encodes for 2 critical tumor suppressor proteins, p16 INK4a and p14 ARF .…”
mentioning
confidence: 99%
“…Although a high expression of cyclin D1 has been related to malignant transformation in melanocytic tumors, a variable or even a high expression of cyclin D1 has been observed in some nevus subtypes, such as Spitz and dysplastic nevi, in contrast to common acquired or congenital nevi, which usually show a low expression of this marker. 2,14,25 Both p16INK4 and p27KIP1 are CDK inhibitors and suppress cell cycle progression. Familial melanomas and a subset of sporadic melanomas show deletion or mutation of the CDKN2A gene.…”
Section: Discussionmentioning
confidence: 99%
“…22 A nuclear higher expression of survivin in malignant melanomas has been previously reported, in contrast with benign nevi. 10,14,26 Moreover, this expression has been assessed as a prognostic factor and as a potentially important therapeutic target in melanomas. 19 In our study, nevi did not express this protein, whereas melanomas showed a low but significantly higher expression of it, in accordance with previously published studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation